Teachers Professional Development : Examining the Effectiveness of Ongoing Training Programs for Primary School Teachers in Algeria. - Adjailia Chaima (My University, 2025)
Abstract This study investigates the impact of ongoing professional development programs on the teaching practices of primary school teachers in Algeria, particularly in the context of English language instruction. Using a mixed-methods approach, the research combines quantitative data gathered from a questionnaire administered to 33 teachers with qualitative insights from a semi-structured interview conducted with an English inspector. The research addresses three main questions: How do ongoing training programs impact the teaching practices of primary school teachers in Algeria? What challenges do teachers face in implementing new methods learned in training programs within their classrooms? To what extent do training programs influence primary students’ academic performance and social development? The findings indicate that professional development programs positively influence teaching practices and student engagement, with a stronger impact in urban areas. However, challenges such as lack of resources, insufficient follow-up support, and the relevance of training materials hinder full implementation. The study underscores the importance of context-specific training, continuous support, and professional learning communities in improving the effectiveness of teaching. Based on the findings, the research offers recommendations for enhancing professional development programs and suggests areas for future research. ------------------------- الملخص تهدف هذه الدراسة إلى استكشاف تأثير برامج التطوير المهني المستمر على الممارسات التعليمية للمعلمين في المدارس االبتدائية في الجزائر، وخاصة في سياق تعليم اللغة اإلنجليزية. باستخدام منهجية مختلطة، تجمع الدراسة بين البيانات الكمية المستخلصة من استبيان تم توزيعه على 33 معلمًا، وبين المعلومات النوعية التي تم جمعها من خالل مقابلة شبه هيكلية مع مفتش لغة إنجليزية. تتناول الدراسة ثالثة أسئلة رئيسية: كيف تؤثر برامج التدريب المستمر على الممارسات التعليمية للمعلمين في الجزائر؟ ما هي التحديات التي يواجهها المعلمون في تطبيق األساليب الجديدة المكتسبة من البرامج التدريبية داخل فصولهم؟ إلى أي مدى تؤثر هذه البرامج التدريبية على األداء األكاديمي والتطور االجتماعي للطالب في المدارس االبتدائية؟ تشير النتائج إلى أن برامج التطوير المهني لها تأثير إيجابي على ممارسات التدريس وانخراط الطالب، مع تأثير أكبر في المناطق الحضرية. ومع ذلك، فإن التحديات مثل نقص الموارد، غياب الدعم المستمر، ومالءمة المواد التدريبية تعيق التنفيذ الكامل لهذه األساليب. تسلط الدراسة الضوء على أهمية تدريب مخصص للسياق، والدعم المستمر، وإنشاء مجتمعات تعلم مهني لتحسين فعالية التعليم. بناءًعلى النتائج، تقدم الدراسة توصيات لتحسين برامج التطوير المهني وتقترح محاور للبحوث المستقبلية ------------------- Résumé Cette étude examine l’impact des programmes de développement professionnel continu sur les Pratiques pédagogiques des enseignants du primaire en Algérie, en particulier dans le contexte de L’enseignement de l’anglais. En utilisant une approche méthodologique mixte, la recherche Combine des données quantitatives issues d’un questionnaire administré à 33 enseignants et des Informations qualitatives obtenues lors d’une interview semi-structurée avec un inspecteur D’anglais. La recherche aborde trois questions principales : Comment les programmes de formation Continue influencent-ils les pratiques pédagogiques des enseignants du primaire en Algérie ? Quels Défis les enseignants rencontrent-ils lors de l’implémentation des nouvelles méthodes apprises lors Des formations ? Dans quelle mesure les programmes de formation influencent-ils la performance Académique et le développement social des élèves du primaire ? Les résultats indiquent que les Programmes de développement professionnel ont un impact positif sur les pratiques pédagogiques Et l’engagement des élèves, avec un effet plus marqué dans les zones urbaines. Cependant, des Défis tels que le manque de ressources, l’absence de suivi adéquat et la pertinence des supports de Formation freinent une mise en œuvre complète. L’étude souligne l’importance d’une formation Spécifique au contexte, d’un soutien continu et de communautés d’apprentissage professionnel pour Améliorer l’efficacité de l’enseignement. Sur la base des résultats, la recherche propose des Recommandations pour améliorer les programmes de développement professionnel et suggère des Axes pour de futures recherches.
Keywords: Professional Development; Teaching Practices; Teacher Training; Primary Education; Algeria; التطوير المهني، الممارسات التعليمية، تدريب المعلمين، التعليم االبتدائي، الجزائر: Développement professionnel; Pratiques pédagogiques; Formation des enseignants; Éducation primaire; Algérie